Angioedema, an uncommon side effect of Ace-Inhibitor use - Shaista U Ahmed; Ayobami Akenroye And Matthew McNabney (Archive of Gerontology and Geriatrics Research - Peertechz Publications, 2018)
Angioedema is a rare but life-threatening side effect of angiotensin-converting enzyme inhibitor (ACEI). It can lead to airway compromise which can be fatal if not treated emergently. CASE: A 69-year-old woman presented to the ED with swollen lips, tongue and change of voice. Her home medications included aspirin, amlodipine, lisinopril and atorvastatin. She was treated with intravenous corticosteroids, diphenhydramine and famotidine. Fiberoptic laryngoscopy showed swollen base of the tongue and arytenoid process necessitating intubation for airway protection. Two units of fresh frozen plasma was given for persistent swelling. Her condition improved, she was extubated and discharged home on the third day. Possible causes of angioedema in her case were food- related, hereditary AE (HAE), and drug -induced. Aspirin and amlodipine related angioedema present early after initiation of these medications. In addition, these drugs typically lead to mast-cell mediated angioedema which is typically associated with a pruritic urticaria. By exclusion, this episode of angioedema was attributed to lisinopril. She was discharged home on aspirin and amlodipine and had no problems on follow up visit.  Angioedema associated with ACEI can occur years after initiation, is usually self- limited and rarely fatal. Prompt recognition and immediate treatment with standard therapy is usually sufficient. Laryngoscopy and early intubation when necessary are critical steps in y management of these patients. Fresh-frozen plasma has been used off -label use in refractory cases of angioedema and has shortened the time to resolution of angioedema complications.